PENGARUH PENGGUNAAN VIDEO TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Budi Nurcahyo; Rini Rita T Marpaung; Berti Yolida (Universitas Lampung, 2017)
The purpose of this research was to know the influence of utilizing video for activity and learning outcomes students. The research design was pretest-posttest not equivalent. Samples were students of class VIIJ and class VIIk at SMPN 21 Bandar Lampung that were 59 students by using purposive sampling technique. Quantitative data were obtained from learning outcomes that were analyzed by U-test. The result of U-test and t-test was t1-test (4,314 1,671) and t2-test (21,174 1,695). Value of U-test showed that value of pretest experiment value was p(0,270 0,157), value of posttest experiment was p (0,000 0,157), and value of experiment N-gain was p (0,000 0,157). Qualitative data was the result of students activity observation and questionaire of students response. Result of research indicated that students activity on experiment class was higher than control that was 12,46%. Most of students gave positive respond about the video. This research showed that utilization of video influence the activities and students learning outcomes.Penelitian bertujuan mengetahui pengaruh penggunaan video terhadap aktivitas dan hasil belajar siswa. Desain penelitian ini adalah pretes-postes tak ekuivalen. Sampel penelitian adalah siswa kelas VIIJ dan kelas VIIK di SMPN 21 Bandar Lampung sebanyak 59 siswa dengan menggunakan teknik purposive sampling. Data kuantitatif diperoleh dari hasil belajar yang dianalisis menggunakan uji-t dan uji-U. Uji-t1 (4,314 1,671) dan untuk uji-t2 (21,174 1,695), Hasil uji-U diperoleh nilai pretes eksperimen p(0,270 0,157), nilai postes eksperimen p(0,000 0,157), dan nilai N-gain eksperimen p (0,000 0,157). Data kualitatif diperoleh dari pretes-postes berupa hasil observasi aktivitas dan angket tanggapan siswa. Hasil penelitian menunjukkan aktivitas siswa pada kelas eksperimen lebih tinggi 12,46% dari kelas kontrol. Sebagian besar siswa memberikan tanggapan positif terhadap penggunaan video. Penelitian ini menunjukkan bahwa penggunaan videoberpengaruh terhadap aktivitas dan hasil belajar siswa.Kata kunci: aktivitas, ciri-ciri makhluk hidup, hasil belajar